A study to assess the benefits of the handbook and the need for it : a qualitative study as part of composing the handbook of maintenance planning - Hyvärinen, Juho (My University, 2025)
The challenges of climate change force us all to act and this also creates new business opportunities. One of the opportunities is storing and optimising the energy in the electric grids and releasing it as needed. Wärtsilä Energy Storage & Optimisation -business is answering this emerged need. The need has pushed the business to steep growth as well as the different teams and the maintenance planning teams working globally, on which this thesis work is focusing. This thesis is done in cooperation between Wärtsilä and University of Turku in two sections. For satisfying academic needs as well the company needs. The sections are divided into this thesis work and the composition of the handbook if proposed so. This thesis work addresses the growth of the maintenance planning team and specifically the importance of onboarding of newcomers which is reflected against the literature. The onboarding process has a major effect on company turnover if executed inefficiently or otherwise neglected. The initiative of composing the handbook of maintenance planning is given by individual employee and therefore this initiative needs to be evaluated to be founded as a plausible way to address the so-called growing pains of the company which are stated as part of the hypothesis or alternatively objecting to the argument. This thesis designs, evaluates and deploys a global survey among the maintenance planners to address their past and current experiences and to obtain their current views of how the knowledge is being managed and what risks they recognise. The conclusions after the evaluation process are that, with some deviation between the respondent groups, they all do recognise a moderate need for having the specified supportive material in their daily work, such as the handbook of maintenance planning. The thesis proposes the composition of specified onboarding material to begin and underlines the importance of keeping the material up to date to address the onboarding process challenges in the near future.
Keywords: survey, handbook, onboarding, socialisation, knowledge management